Analysis of the potential of innovation in dressings to treat chronic wounds in the city of Lima, Peru. - Casado, Fanny L. (2020)
Objective: To analyze the potential for innovation in dressings to treat chronic wounds in the City of Lima.  Methods: A qualitative study was carried out by means of interviews to medical experts and purchasing managers of medical supplies for the treatment of difficult-to-resolve wounds in 8 representative public health institutions with categories 1-4 within the only  54 of Lima, Peru - 2018. Results: It was determined that an average of 17 patients is treated in public health institutions on a monthly basis (60% from hospitalization and 40% from an outpatient office). It is equivalent to say that 11,016 patients present chronic wounds of difficult resolution each year, which will require specialized treatment and an average annual demand of 110,160 dressings in stock. The dressings with the highest demand correspond to the Hydrogels and Hydrocolloids, respectively; used because of the positive results they offer in wound healing, despite economic limitations. The market  price per unit ranges between 20 and 90 soles (S/.), representing an economic investment of 1500 soles on average per patient, in some cases causing complications or abandonment of treatment when resources are scarce. Conclusions: There is a high demand for patients with chronic wounds of difficult resolution in the public health institutions of Lima. It is important to promote and incentivize the investigation of new therapeutic alternatives and / or biomedical devices that favor its treatment.